2011
DOI: 10.1111/j.1365-2648.2011.05633.x
|View full text |Cite
|
Sign up to set email alerts
|

How nursing staff spend their time on activities in a nursing home: an observational study

Abstract: Nursing staff value their face-to-face interaction for successful care delivery. There is need, however, to investigate the effects of this form of communication on quality of care given to residents. Differences in multi-tasked activities between high care and low care houses should be considered when deploying staff in a nursing home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
3
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 19 publications
8
77
3
14
Order By: Relevance
“…Previous studies 6,15,18 only presented the total direct care time, which was consistent with the first point presented above, but did not address the other points. The present study has advanced knowledge by providing more detailed information about each direct care activity.…”
Section: Common Findings At Both Racfssupporting
confidence: 73%
See 3 more Smart Citations
“…Previous studies 6,15,18 only presented the total direct care time, which was consistent with the first point presented above, but did not address the other points. The present study has advanced knowledge by providing more detailed information about each direct care activity.…”
Section: Common Findings At Both Racfssupporting
confidence: 73%
“…25 Several previous studies in healthcare settings, including RACFs, have suggested that the Hawthorne effect is not significant in direct observation; 6,26,27 consequently, we did not measure it in the present study.…”
Section: Limitationsmentioning
confidence: 72%
See 2 more Smart Citations
“…(12,13) The time spent with the displacement of staff (indirect assistance), demanded 65.3 hours of the total of 157.3 hours of timed home care. It is noteworthy that the service infrastructure needs to be revised, especially that related to transportation for transit of professionals.…”
Section: Discussionmentioning
confidence: 99%